Kaizen-21 : the philosophy of continuous improvement and operational innovation in the new global environment - Suárez-Barraza, Manuel F. (Emerald points., 2023)
Since Masaki Imai connected the term KAIZEN with the world management arena in 1986, this approach has been used as a strategy for company development that is propelled by the participation and motivation of its employees. Centering the human being as the guiding axis of change and innovation, KAIZEN-21 establishes a practical and theoretical guide for organizations to easily implement this ancestral philosophy within their operational processes in the midst of the chaotic and complicated global environment of the 21st century. Presenting an updated model of guiding principles, techniques, and tools, Manuel F. Suárez Barraza demonstrates how KAIZEN can be successfully applied in the context of pandemics, supply chain crises, and regional war. Beginning with the definition and origins of KAIZEN, chapters explore 5'S, standardization (Hiojunka), SDCA and PDCA cycles, as well as process innovation and kodawari-KAIZEN, or hitosukuri (management of people), closing with techniques for improving daily work, such as the the Kata of Improvement, and the author's links with the Toyota Production System (TPS) and the Mayan work model (K'AAT-KAIZEN). If you are ready to energize your business team and revolutionize workplace practices, then KAIZEN-21 is your essential resource for prioritizing internal change and development despite all adversity.